2000
DOI: 10.1074/jbc.m001389200
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y and Sp1 Cooperate for the Transcriptional Activation and cAMP Response of Human Tissue Inhibitor of Metalloproteinases-2

Abstract: The balance between matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs) is a key determinant in the homeostasis of the extracellular matrix. We have identified two cis-acting elements involved in the transcriptional regulation of TIMP-2. The first is an inverted CCAAT box located at position ؊73 to ؊69 in the TIMP-2 promoter that binds the transcription factor NF-Y. The second is a GAGGAGGGGG motif located at position ؊107 to ؊98, that binds the transcription factors Sp1 and Sp3. NF-Y and Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
4
35
1
Order By: Relevance
“…A representation of the DNA double helices as found in the energy-minimized average structures of the modelled EGR1/mdr1 (left) and Sp1/mdr1 (right) complexes. Note that the long helical axes, as calculated by CURVES, 97 are virtually straight in both cases. Distances are in Å and angles are in degrees.…”
Section: Dna Bendingmentioning
confidence: 81%
“…A representation of the DNA double helices as found in the energy-minimized average structures of the modelled EGR1/mdr1 (left) and Sp1/mdr1 (right) complexes. Note that the long helical axes, as calculated by CURVES, 97 are virtually straight in both cases. Distances are in Å and angles are in degrees.…”
Section: Dna Bendingmentioning
confidence: 81%
“…Within this region of the promoter, there are several full consensus binding sites for transcription factors such as SP1, NFY, and AP1, and DNA binding assays confirmed that SP1 and NFY bind the Brn-2 promoter in vitro (not shown). Since these factors are known to be Ras and MAP kinase responsive (1,23,40,42,43), it is likely that the ability of Ras to activate Brn-2 expression is mediated at least in part by the combination of these factors acting in concert at the promoter.…”
Section: Resultsmentioning
confidence: 99%
“…SP1 has also been implicated in the activation of the TIMP1 (46), TIMP2 (47), and Timp4 (48) genes, raising the possibility that P14ARF and SP1 might exert coordinated antiangiogenic effects through other members of the TIMP family. This was not the case, as our data show that TIMP1 and TIMP2 levels remained unchanged by P14ARF.…”
Section: Figurementioning
confidence: 99%